Antitumor activity of cell‐penetrant kinin B1 receptor antagonists in human triple‐negative breast cancer cells. Issue 3 (21st August 2018) - Dubuc, Céléna; Savard, Martin; Bovenzi, Veronica; Lessard, Andrée; Côté, Jérôme; Neugebauer, Witold; Geha, Sameh; Chemtob, Sylvain; Gobeil, Fernand
Abstract : High nuclear expression of G protein‐coupled receptors, including kinin B1 receptors (B1R), has been observed in several human cancers, but the clinical significance of this is unknown. We put forward the hypothesis that these "nuclearized" kinin B1R contribute to tumorigenicity and can be a new target in anticancer strategies. Our initial immunostaining and ultrastructural electron microscopy analyses demonstrated high B1R expression predominantly located at internal/nuclear compartments in the MDA‐MB‐231 triple‐negative breast cancer (TNBC) cell line as well as in clinical samples of patients with TNBC. On the basis of these findings, in the present study, we evaluated the anticancer therapeutic potential of newly identified, cell‐permeable B1R antagonists in MDA‐MB‐231 cells (ligand–receptor binding/activity assays and LC‐MS/MS analyses). We found that these compounds (SSR240612, NG67, and N2000) were more toxic to MDA‐MB‐231 cells in comparison with low‐ or non‐B1R expressing MCF‐10A normal human mammary epithelial cells and COS‐1 cells, respectively (clonogenic, MTT proliferative/cytocidal assays, and fluorescence‐activated cell‐sorting (FACS)‐based apoptosis analyses). By comparison, the peptide B1R antagonist R954 unable to cross cell membrane failed to produce anticancer effects. Furthermore, the putative mechanisms underlying the anticancer activities of cell‐penetrant B1R antagonists were assessed by analyzing cell cycle regulation and signaling molecules related to cell survival and apoptosis (FACS and western blot). Finally, drug combination experiments showed that cell‐penetrant B1R antagonists can cooperate with suboptimal doses of chemotherapeutic agents (doxorubicin and paclitaxel) to promote TNBC death. This study provides evidence on the potential value of internally acting kinin B1R antagonists in averting growth of breast cancer. Abstract : High nuclear localization of G protein‐coupled receptors (GPCRs) has been observed in several human cancers, but the clinical significance of this remains unknown. Here, we provided in vitro evidence for the existence of a novel intracrine signaling pathway mediated by nuclear kinin B1 receptors, critical for the growth of triple‐negative breast cancer (TNBC) cells, and identifed new chemical entities that enable to target the corresponding intracellular GPCRs. In sum, our results highlight the need to target a given GPCR in relation to its subcellular localization to achieve therapeutic outcomes.